Characterization of Freeze-Drying Methods for Plant-Based Foods - Pawestri, Setyaning; Syahbanu, Fathma (Agros Journal of Agriculture Science, 2023)
Freeze-drying is widely used to dry plant-based foods, including fruits, vegetables, herbs, and nontraditional foods. Even though it requires a long processing time and is expensive, the freeze-drying method is preferred because it can produce high-quality food products. This is because the freeze-drying method can maintain nutritional quality compared to other dehydration methods, especially if operated under vacuum conditions. Freeze-drying conditions will affect various food ingredients' nutritional properties and antioxidant activity. However, inappropriate selection of process parameters can cause undesirable changes in the product, such as shrinkage, colour changes, and damaged structure. This review manuscript aims to characterize the freeze-drying of plant-based foods and explain the influence of processing conditions on selected physical properties of different food products.